Recruitment of Dynamic Endothelial Ca(2+) Signals by the TRPA1 Channel Activator AITC in Rat Cerebral Arteries - Qian, Xun (2013)
OBJECTIVE: Stimulation of endothelial TRP channels, specifically TRPA1, promotes vasodilation of cerebral arteries through activation of Ca(2+)-dependent effectors along the myoendothelial interface. However, presumed TRPA1-triggered endothelial Ca(2+) signals have not been described. We investigated whether TRPA1 activation induces specific spatial and temporal changes in Ca(2+) signals along the intima that correlate with incremental vasodilation. METHODS: Confocal imaging, immunofluorescence staining and custom image analysis were employed. RESULTS: We found that endothelial cells of rat cerebral arteries exhibit widespread basal Ca(2+) dynamics (44 ± 6 events/minute from 26 ± 3 distinct sites in a 3.6x10(4) μm(2) field). The TRPA1 activator AITC increased Ca(2+) signals in a concentration-dependent manner, soliciting new events at distinct sites. Origination of these new events corresponded spatially with TRPA1 densities in IEL holes, and the events were prevented by the TRPA1 inhibitor HC-030031. Concentration-dependent expansion of Ca(2+) events in response to AITC correlated precisely with dilation of pressurized cerebral arteries (p = 0.93 by F-test). Correspondingly, AITC caused rapid endothelium-dependent suppression of asynchronous Ca(2+) waves in subintimal smooth muscle. CONCLUSIONS: Our findings indicate that factors that stimulate TRPA1 channels expand Ca(2+) signal-effector coupling at discrete sites along the endothelium to evoke graded cerebral artery vasodilation.